2020
DOI: 10.1186/s40510-020-00333-5
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional variability of orthodontic slots and archwires: an analysis of torque expression and clinical implications

Abstract: Background The loss of third-order information in pre-adjusted brackets due to torsional play is a problem in clinical orthodontics. The aim of this study was to evaluate the impact of slot height, archwire height, width and edge bevel’s radius on the torsional play for three brackets/archwire systems. Methods Ninety brackets with a 0.022 × 0.028 in. slot with McLaughlin-Bennett-Trevisi prescription from three different manufacturers were selected, and the slot’s height and depth were measured using a profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
2
12
1
2
Order By: Relevance
“…Although according to the norm, undersized slots within the tolerance limits are considered acceptable, from a practical standpoint, they could impede the correct seating of a full size wire that has a nominal cross section that is equal to the nominal slot size [ 21 ]. In a clinical setting, the full size arch can seat also in the case of undersized slots, taking into account that contemporary archwires are usually undersized when compared to their nominal value [ 23 ]. The high prevalence of oversize slots can be partly due to a failure in calculating the actual shrinkage after sintering or by a lack of control in the final polishing phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although according to the norm, undersized slots within the tolerance limits are considered acceptable, from a practical standpoint, they could impede the correct seating of a full size wire that has a nominal cross section that is equal to the nominal slot size [ 21 ]. In a clinical setting, the full size arch can seat also in the case of undersized slots, taking into account that contemporary archwires are usually undersized when compared to their nominal value [ 23 ]. The high prevalence of oversize slots can be partly due to a failure in calculating the actual shrinkage after sintering or by a lack of control in the final polishing phase.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramic brackets were not included in the current study either. All measurements were performed from the distal side not assessing the mesial one, although all previous studies analysed only one side [ 10 , 12 , 13 , 22 , 23 ], this protocol can hinder the slot dimensional asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…archwire in a bracket slot of 0.022 in. [16]. Arreghini et al (2014) found a torsional play ranging from 13.80 • ± 0.12 • to 28.68 • ± 0.48 • while engaging a 0.019 × 0.025 in.…”
Section: Torquementioning
confidence: 99%
“…(Cattaneo et al 2013) Es así que en ortodoncia "el torque se refiere a la inclinación bucolingual de las coronas de los dientes anteriores y posteriores, influyendo de esta manera en: La oclusión sagital óptima, permitiendo una clase I molar, la longitud ideal del arco" según Hussel y Nanda, aportar positivamente en la estética dental según Ghabel y cols. (Dalstra et al 2015;Tepedino et al 2020)Una mala inclinación labiolingual de los dientes especialmente los anteriores provocaría una disminución en la longitud del arco, y de esta forma se perdería espacio; es decir por cada 5° de inclinación en el sector anterior implica 1mm de afección en la longitud total del arco. (Badawi et al 2008;Katsikogianni et al 2015) Lo que sucede en el sector posterior será un estrechamiento, de esta manera no existirá una relación adecuada entre las cúspides superiores con las inferiores.…”
Section: Brackets De Autoligado Pasivounclassified